Quality Improvement Management in Preparing Graduates to Enter State Universities - Tri Yulinda Narayanti; Didin Wahidin; N. Dede Koeriah; Helmawati (International Journal of Science Education and Technology Management, 2023)
High School is an educational institution that is very important for the nation's children. SMA as a formal institution that aims to educate is very heavy responsibility. Because high school students are expected to be able to live independently and continue to higher education, namely college. Although many universities in Indonesia are private and public, the number of students who are recruited by state universities in a high school is considered to improve the quality of the school. So this study aims to determine: 1). How is management planning to improve the quality of graduates who enter state universities at SMAN 29 Jakarta, SMAN 32 Jakarta and SMA SMAN 86 Jakarta, 2). How is the implementation of management to improve the quality of graduates who enter state universities at SMAN 29 Jakarta, SMAN 32 Jakarta and SMA SMAN 86 Jakarta, 3). How to evaluate the quality of management to improve the quality of graduates who enter state universities at SMAN 29 Jakarta, SMAN 32 Jakarta and SMA SMAN 86 Jakarta 4). What are the management barriers to improving the quality of graduates who enter state universities at SMAN 29 Jakarta, SMAN 32 Jakarta and SMA SMAN 86 Jakarta 5). What is the solution to the management problem of improving the quality of graduates who enter state universities at SMAN 29 Jakarta, SMAN 32 Jakarta and SMA SMAN 86 Jakarta.